Literary genres in English textbooks for Senior High School - Aulia, Dhini; Yusuf, Fazri Nur; Sukyadi, Didi; Aziz Lubis, Azhar (Universitas Muhammadiyah Sidoarjo, 2024)
While the potential of literary works in English as a Foreign Language (EFL) education is often discussed, limited research exist on their integration into Indonesian senior high schools English textbooks. The present study investigates how literary genres are incorporated into English textbooks in Indonesian senior high schools by investigating (1) the literary genre described in the textbooks and (2) the tasks that describe the language skills and the literary - specific knowledge to recognize the critical role of such content in fostering students' language development, cultural and intercultural awareness, and engagement in EFL education. The data sources of this study were three levels of senior high school English student textbooks published by the Indonesian government. The study combined a quantitative approach to examine the presence of literary works with qualitative content analysis to unpack the language skills and literary-specific knowledge included in the textbooks. The framework utilized literary genre terms and literary-specific knowledge. Among the 31 chapters in the textbooks, 12 chapters (39%) addressed literary works from various cultures, with 53% of the texts derived from the Indonesian context. In addition to language skills activities and tasks, there were literary knowledge activities. These findings implied that improving students' cultural and intercultural awareness may pose challenges. Moreover, these results highlight the importance of incorporating more authentic English literary works into English textbooks to prepare students for real - world English cultures. HIGHLIGHTS: The literary genres represented in these textbooks include fiction, nonfiction, and poetry. The authors of the analyzed textbooks predominantly utilized the term “genre-based text”,including narrative and recount texts, without introducing the term “literary" or "sastra". Over 53% of the literary content in these textbooks consists of texts or stories in anIndonesian context, so educators should include learning materials that feature originalliterary works to increase students' exposure to Western culture.